Contribution of integrin adhesion to cytokinetic abscission and genomic integrity - Rani, Bhavna; Gupta, Deepesh K.; Johansson, Staffan; Kamranvar, Siamak A. (Frontiers in Cell and Developmental Biology, 2022)
Recent research shows that integrin-mediated adhesion contributes to the regulation of cell division at two key steps: the formation of the mitotic spindle at mitotic entry and the final cytokinetic abscission. Failure in either of these processes will have direct consequences for the other in each round of the cell cycle, and for the genomic integrity. This review aims to present how integrin signals are involved at these cell cycle stages under normal conditions and some safety mechanisms that may counteract the generation of aneuploid cells in cases of defective integrin signals.